Non–Prostate-Specific Membrane Antigen-Avid Metastatic Lung Nodule From Primary Prostatic Adenocarcinoma. (October 2016) - Shetty, Deepa; Loh, Han; Bui, Chuong; Mansberg, Robert; Hadjashrafi, Amirazin; Do, Viet
Abstract : Abstract: 68 Ga-prostate-specific membrane antigen (PSMA) PET/CT is increasingly used to evaluate recurrent prostatic malignancy due to its high specificity. A 56-year-old man with previous history of treated prostate cancer 4 years earlier presented with rising prostate-specific antigen level and underwent 68 Ga-PSMA PET/CT, which demonstrated an enlarging pulmonary nodule without PSMA avidity. The pulmonary nodule, however, showed moderate uptake on a corresponding FDG PET/CT study, suspicious of primary lung malignancy. Cytological and histopathological examination of the pulmonary nodule confirmed a metastatic deposit from ductal prostatic adenocarcinoma, an uncommon variant of prostatic malignancy.